2018
DOI: 10.1038/s41523-018-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic characteristics in hormone receptor-positive advanced breast cancer and characterization of abemaciclib efficacy

Abstract: CDK4 & 6 inhibitors have enhanced the effectiveness of endocrine therapy (ET) in patients with advanced breast cancer (ABC). This paper presents exploratory analyses examining patient and disease characteristics that may inform in whom and when abemaciclib should be initiated. MONARCH 2 and 3 enrolled women with HR+, HER2- ABC. In MONARCH 2, patients whose disease had progressed while receiving ET were administered fulvestrant+abemaciclib/placebo. In MONARCH 3, patients received a nonsteroidal aromatase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 26 publications
2
27
0
2
Order By: Relevance
“…Di Leo et al performed an interesting exploratory analysis, examining patient and disease characteristics to identify the patients most likely to benefit from abemaciclib and the best time to initiate treatment [ 24 ]. The analysis of clinical factors showed that bone-only disease, liver metastases, tumor grade, PR expression, performance status, treatment-free interval from the end of adjuvant endocrine therapy, and time from diagnosis to recurrence had a prognostic value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Leo et al performed an interesting exploratory analysis, examining patient and disease characteristics to identify the patients most likely to benefit from abemaciclib and the best time to initiate treatment [ 24 ]. The analysis of clinical factors showed that bone-only disease, liver metastases, tumor grade, PR expression, performance status, treatment-free interval from the end of adjuvant endocrine therapy, and time from diagnosis to recurrence had a prognostic value.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of clinical factors showed that bone-only disease, liver metastases, tumor grade, PR expression, performance status, treatment-free interval from the end of adjuvant endocrine therapy, and time from diagnosis to recurrence had a prognostic value. Patients with poor prognostic factors showed the greatest benefit from the addition of abemaciclib [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of liver metastases (in 18% of EU5 women providing PRO data) was not an independent predictor of HRQoL in our regression analysis. Analyses of phase III studies aimed at identifying which subgroup of patients may benefit most from a combination of ET plus CDK4 & 6 inhibitor as initial therapy for advanced disease found that patients with indicators of a poor prognosis (liver metastases, progesterone receptor-negative tumors, high-grade tumors, or treatment-free interval < 36 months) benefited most from this combination therapy [ 49 ]. Thus, greater use of ET plus a CDK4 & 6 inhibitor as initial therapy for advanced disease in women with HR+/HER2− advanced breast cancer may have the potential to maintain/improve patient HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…1 и 2); в то же время при наличии определенных факторов благоприятного прогноза, таких как интервал без лечения после окончания ЭТ ≥ 36 мес., метастазирование только в кости, на одной только ЭТ медиана ВБП превышала 20 мес. [70]. Таким образом, комбинация абемациклиба с ЭТ по сравнению с одной только ЭТ значимо повышает эффективность лечения пациентов с неблагоприятным течением заболевания и высоким риском быстрого прогрессирования болезни как в 1-й, так и во 2-й линиях лечения.…”
Section: эффективность абемациклиба у пациентов с неблагоприятными прunclassified